Public Health Surveillance via Template Management in Electronic Health Records: Tri-Service Workflow's Rapid Response to an Infectious Disease Crisis. (1st March 2017) - Berkley, Holly; Barnes, Matthew; Carnahan, David; Hayhurst, Janet; Bockhorst, Archie; Neville, James
ABSTRACT: Objective: To describe the use of template-based screening for risk of infectious disease exposure of patients presenting to primary care medical facilities during the 2014 West African Ebola virus outbreak. Methods: The Military Health System implemented an Ebola risk-screening tool in primary care settings in order to create early notifications and early responses to potentially infected persons. Three time-sensitive, evidence-based screening questions were developed and posted to Tri-Service Workflow (TSWF) AHLTA templates in conjunction with appropriate training. Data were collected in January 2015, to assess the adoption of the TSWF-based Ebola risk-screening tool. Results: Among encounters documented using TSWF templates, 41% of all encounters showed use of the TSWF-based Ebola risk-screening questions by the fourth day. The screening rate increased over the next 3 weeks, and reached a plateau at approximately 50%. Conclusions: This report demonstrates the MHS capability to deploy a standardized, globally applicable decision support aid that could be seen the same day by all primary care clinics across the military health direct care system, potentially improving rapid compliance with screening directives.